Izvedba rekurzivnih digitalnih sit s PLC krmilnikom - Dodić, Aleksandar (Informacije MIDEM, 2008)
In this paper the design and realization of first, second and third order recursive digital filter (IIR digital filter) with PLC controller is described. The purpose of the filter structure is eliminating unwanted signals at processing of analog signals in industrial proccess automation with PLC controllers. In practical realization the Siemens S7-315-2DP PLC controller is used. In this application the eliptical filter is chosen, cuff-off frequency was 3 Hz and sampling frequency was 50 Hz. With format long values of filter coefficients we obtain the expected stop band attenuation of 40 dB as is designed with MATLAB software. For the comparision of PLC controller realization of digital filter and simulated structure with MATLAB, the obtained values of impulse response are used. The results are sumarised in Table 2 for second order digital filter for format long and shortened mode format of coefficients entry and in Table 5 for third order digital filter only for format long coefficients. In fig. 1 the magnitude response of the empiric digital filter is shown for different values of smoothing parameter k. In fig. 2, 3 and 6 the masks as a part of the organization block of Siemens PLC controler for entry of the coefficients and input variables for the first, second an third order digital filter structure are presented. In fig. 4 the magnitude frequency response of 2nd order low pass eliptic IIR filter with cut-off frequency of 3 Hz is shown. The third order recursive filter is designed as caskaded form with cascade structures of the first and the second order. For this operation the MATLAB FDA toolbox is used for second order structure (SOS structure) calculation. The first and second order structures for eliptic recursive digital filter the SOS matric is presented in equation (10) and in fig. 5 the general cascade realization of two structures recursive digital filter for third and also for fourth order digital filters is shown. The impulse response and the magnitude frequency response of 3d order eliptic IIR digital filter with cut off frequency of 3 Hz are shown in Fig. 7 and 8 respectively. In comparison to the second order digital filter where the attenuation of 40 dB is obtained at 15 Hz with third order digital filter structure the attenuation of 40 dB is obtained at 7 Hz.
Keywords: digitalna obdelava signalov; filtri; krmilniki; motnje; programirni logični krmilniki